A Comparison of Digitized Frozen Section and Smear Preparations for Intraoperative Neurotelepathology - Peter V. Gould; Stephan Saikali (Analytical Cellular Pathology)
Background: Intraoperative consultations in neuropathology are often assessed by smear preparations rather than by frozen sections. Both techniques are standard practice for light microscopic examination on site, but there is little data comparing these techniques in a telepathology setting.